Early Buddhist Transmission and Trade Networks Mobility and Exchange within and beyond the Northwestern Borderlands of South Asia - Neelis, Jason (Dynamics in the History of Religions, 2010)
This book examines catalysts for Buddhist formation in ancient South Asia and expansion throughout and beyond the northwestern Indian subcontinent to Central Asia by investigating symbiotic relationships between networks of religious mobility and trade. Readership: Readers with interests in the history of Buddhism, South Asian religions and economy, premodern trade routes, cultural geography, and cross-cultural interactions between India, Central Asia, Iran, and the Hellenistic world.